Synthesis of lipid mediators during UVB-induced inflammatory hyperalgesia in rats and mice. - Marco Sisignano; Carlo Angioni; Nerea Ferreiros; Claus-Dieter Schuh; Jing Suo; Yannick Schreiber; John M Dawes; Ana Antunes-Martins; David L H Bennett; Stephen B McMahon; Gerd Geisslinger; Klaus Scholich (PLoS ONE, 2013)
Peripheral sensitization during inflammatory pain is mediated by a variety of endogenous proalgesic mediators including a number of oxidized lipids, some of which serve endogenous modulators of sensory TRP-channels. These lipids are eicosanoids of the arachidonic acid and linoleic acid pathway, as well as lysophophatidic acids (LPAs). However, their regulation pattern during inflammatory pain and their contribution to peripheral sensitization is still unclear. Here, we used the UVB-model for inflammatory pain to investigate alterations of lipid concentrations at the site of inflammation, the dorsal root ganglia (DRGs) as well as the spinal dorsal horn and quantified 21 lipid species from five different lipid families at the peak of inflammation 48 hours post irradiation. We found that known proinflammatory lipids as well as lipids with unknown roles in inflammatory pain to be strongly increased in the skin, whereas surprisingly little changes of lipid levels were seen in DRGs or the dorsal horn. Importantly, although there are profound differences between the number of cytochrome (CYP) genes between mice and rats, CYP-derived lipids were regulated similarly in both species. Since TRPV1 agonists such as LPA 18∶1, 9- and 13-HODE, 5- and 12-HETE were elevated in the skin, they may contribute to thermal hyperalgesia and mechanical allodynia during UVB-induced inflammatory pain. These results may explain why some studies show relatively weak analgesic effects of cyclooxygenase inhibitors in UVB-induced skin inflammation, as they do not inhibit synthesis of other proalgesic lipids such as LPA 18∶1, 9-and 13-HODE and HETEs.